2017
DOI: 10.1002/bdr2.1052
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Sodium Valproate during Pregnancy: Facial Features and Signs of Autism

Abstract: BACKGROUND Valproic acid (VPA) is the most teratogenic anticonvulsant drug in clinical use today. Children exposed prenatally to VPA have previously been shown to have dysmorphic craniofacial features, identified subjectively but not by anthropometric methods. Exposure to VPA has also been associated with an increased frequency of Autism Spectrum Disorder (ASD). An increased cephalic index (the ratio of the cranial lateral width to the cranial anterior-posterior length) has been observed in children with ASD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 63 publications
(71 reference statements)
0
21
0
3
Order By: Relevance
“…In the same lines, a recent study showed that valproic acid-exposed children during the first trimester of pregnancy compared to the unexposed children had a large cephalic index. The large cephalic index was present in valproic acid-exposed children both with and without ASD (Stadelmaier et al 2017).…”
Section: Current Knowledgementioning
confidence: 91%
“…In the same lines, a recent study showed that valproic acid-exposed children during the first trimester of pregnancy compared to the unexposed children had a large cephalic index. The large cephalic index was present in valproic acid-exposed children both with and without ASD (Stadelmaier et al 2017).…”
Section: Current Knowledgementioning
confidence: 91%
“…Due to the significant risk of birth defects and developmental disorders in babies born to mothers taking VPA during pregnancy, the MHRA have issued guidance advising: ‘Valproate medicines must no longer be used in women or girls of childbearing potential unless a Pregnancy Prevention Programme is in place’. Women of childbearing potential (WOCBP) will not be recruited to the trial, due to known teratogenic effects of VPA [ 22 ]. All women will require a follicular stimulating hormone (FSH) test prior to randomisation, to confirm post-menopausal status.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…To be useful for exposure cohort studies, pregnancy registries and teratogen information services must collect Reference: Hill, 1965. data from unexposed control pregnancies in the same manner as exposed pregnancies (Chambers et al, 1996(Chambers et al, , 2016. A few pregnancy registries and teratogen information services also collect data on the children in sufficient detail and with sufficient rigor to permit recognition of recurrent patterns of congenital anomalies (Cassina et al, 2012;Stadelmaier et al, 2017), something that is rarely possible in other kinds of epidemiology studies.…”
Section: Cohort Studiesmentioning
confidence: 99%